Direction of Umbilical Cord Twist and its Characteristics - a Pilot Study - Althea V. Pinto; Alex X. Chakiath; Prudhvi Dasari; Vilekith Reddy; Shirley George; Nachiket Shankar (University Library System, University of Pittsburgh, 2013)
Background: A right-sided umbilical cord twist is associated with the presence of a single umbilical artery, congenital malformations and placenta praevia. Methods: It was an observational study. Data was collected from 137 umbilical cords, all from live births and their patient records. The gestational ages ranged from 28 weeks to 41 weeks. The umbilical cords were categorized into right or left, based on the direction of twist. The independent sample T test and the Chi square test were used to analyze the differences between groups. Results: The prevalence of left twist was 84%. Right twist was significantly associated with a larger Hyrtl's anastomosis (p=0.029) and gestational diabetes (p=0.027). Conclusion: Two previously unreported associations with right twist of the umbilical cord, gestational diabetes and an increase in the diameter of Hyrtl's anastomosis, were noted in the present study.